POTENSI OBJEK WISATA BAHARI PESISIR PANTAI DI KOTA PARIAMAN SUMATERA BARAT - Yenida Yenida; Zaitul Ikhlas Saad (Jurnal Ilmiah Poli Bisnis, 2018)
Pariaman City is one of the cities located in West Sumatra. Geographically, most of the area are located on coastal areas. Two thirds of Pariaman City are coastal areas. Therefore Pariaman City area has its beautiful natural potencies in the form of beaches, seas and enchanting islands. The purpose of this study is to introduce the natural potential of the marine tourism objects that are found in Pariaman City. Qualitative description approach is used as the research method and purposive sampling is the method of taking samples in this research. Observation, interview, and documentation are used as technique of taking data. The results show that the most visited tourism objects in Pariaman City are Gondoriah Beach, Cermin Beach, Kata Beach, Turtle breeding area, Pauh Beach and also culinary sightseeing places, while other beaches have not been developed well by government